2005
DOI: 10.1345/aph.1g009
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Pharmacists Toward Mental Illness and Providing Pharmaceutical Care to the Mentally III

Abstract: Pharmacists expressed generally positive attitudes toward both mental illness and the providing of pharmaceutical care to mentally ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 10 publications
7
52
0
1
Order By: Relevance
“…Another probable explanation could be pharmacists’ perceived attitudes and barriers to providing pharmaceutical care to mental health patients. Pharmacists have positive attitudes toward both mental illness and the providing of pharmaceutical care to mentally ill patients [20,21]; however, lack of adequate education in mental health issues have been reported as an important barrier to the provision of pharmaceutical care [22]. Surveys of the psychiatric pharmacy curriculum in the USA and Europe showed that the psychiatry-related topics are taught as part of a therapeutics-based course and a fewer number of colleges offer internship in psychiatry [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Another probable explanation could be pharmacists’ perceived attitudes and barriers to providing pharmaceutical care to mental health patients. Pharmacists have positive attitudes toward both mental illness and the providing of pharmaceutical care to mentally ill patients [20,21]; however, lack of adequate education in mental health issues have been reported as an important barrier to the provision of pharmaceutical care [22]. Surveys of the psychiatric pharmacy curriculum in the USA and Europe showed that the psychiatry-related topics are taught as part of a therapeutics-based course and a fewer number of colleges offer internship in psychiatry [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The items on professional service delivery were derived from previous studies on pharmacist attitudes towards mental illness. 12,24 The 16 items relating to stigmatizing beliefs in severe depression and schizophrenia were based on surveys of medical students, physicians, and the public. 25,26 The beliefs included ''have themselves to blame,'' ''unpredictable,'' ''will never recover,'' ''difficult to talk to,'' ''not improve after treatment,'' ''danger to others,'' ''pull themselves together,'' and ''have different feelings.''…”
Section: Survey Instrumentmentioning
confidence: 99%
“…It has been widely evidenced that stigma is not limited to the lay public but also extends to health professionals [5][6][7]; the very people mental health consumers rely on for care. While the literature has largely focused on addressing the mental health stigma held by professionals such as psychiatrists, general medical practitioners and nurses, some studies have identified pharmacists and pharmacy students as important targets for mental health stigma reduction interventions [8][9][10][11]. Medications are a major modality of treatment for most mental illnesses and professional pharmacist services such as counselling and medication reviews can increase adherence to medication and resolve psychotropic medication related problems [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%